High temperature activation of noble metal catalysts supported on carbon multi-walled nanotubes for selective hydrogenation of unsaturated aldehydes - Machado, Bruno (2010)
Selective catalytic hydrogenation of α,β-unsaturated aldehydes represents today an important route in the industrial preparation of fine chemicals. Heterogeneous catalysts are normally less selective than the homogeneous, but easier to handle. Therefore, there is still room for improvement especially regarding catalyst selectivity to the unsaturated alcohol. Our work shows that the surface chemistry also plays an important role on selectivity. We describe an activation procedure for platinum and iridium metal catalysts supported on carbon nanotubes, which improves significantly both selectivity and activity. In the case of platinum, selectivity towards the unsaturated alcohol increased 8 times to a maximum of 66% at 79% conversion.